If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4=2(y-12)
We move all terms to the left:
4-(2(y-12))=0
We calculate terms in parentheses: -(2(y-12)), so:We get rid of parentheses
2(y-12)
We multiply parentheses
2y-24
Back to the equation:
-(2y-24)
-2y+24+4=0
We add all the numbers together, and all the variables
-2y+28=0
We move all terms containing y to the left, all other terms to the right
-2y=-28
y=-28/-2
y=+14
| 2+4a−3a−12+5a=16−2a−7−9+2a | | f/7+-36=-39 | | 2-6d=68 | | -11=t/2+-8 | | y=-0.8+2.5 | | 17x-3=16x | | 1/3x+13=2x-3 | | 8m+6=22 | | 17w+3=5w+9 | | 1+2a−7+9a+5=6a+8a−13+2−3 | | 100=10(b+1) | | j/2-18=-13 | | -26=-6z-7z | | 10x-37=7x-19 | | 2(-4x+2)=3x+26 | | q-(-46)/10=8 | | -4+3m=5 | | 7x+9=10x-2 | | 35=10b=5 | | 5x−9−8x+9=−15x+7+12x−7 | | 2q+13=-3 | | -69=q/9-72 | | 4s-(-38)=98 | | 2k+12=10 | | m/6-1=3 | | -9+8v=-17 | | −5x=−125 | | 36-3x=4+5x | | 6+3a=6 | | 4(k−77)=88 | | 17x+40=25x+50 | | 8x+13=2x-23 |